Analisis Peran Mediasi Kepuasan Kerja Dan Komitmen Organisasi Dalam Hubungan Antara Persepsi Dukungan Organisasional Dan Perilaku Kewargaan Organisasional Pada Karyawan - Haryani Haryani; Jajuk Herawati (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2021)
This study is to examine the effect of perceptions of organizational support on job satisfaction, perceptions of organizational support on organizational commitment, job satisfaction on organizational citizenship behavior, organizational commitment to organizational citizenship behavior, and perceptions of organizational support on organizational citizenship behavior. The research samples came from companies engaged in tourism located in Klaten, Central Java. The sampling method uses total sampling. So that the total sample taken in this study amounted to 50 employees. The sample data collection was carried out by distributing questionnaires in the form of a Google Form which were sent via the employee's WhatsApp number. The number of questionnaire data that was processed was 50 questionnaires. Data processing in this study uses multiple linear regression analysis techniques, assisted by the SPSS program version 16.0. The results of this study indicate that: 1) perceived organizational support has a significant positive effect on job satisfaction, 2) perceived organizational support has a significant positive effect on organizational commitment, 3) job satisfaction has a significant positive effect on organizational citizenship behavior, 4) organizational commitment has a significant positive effect on organizational commitment. organizational citizenship behavior, 5) perceived organizational support has a significant positive effect on organizational citizenship behavior